Triglyceride Glucose Index Was a Predictor of 6-Month Readmission Caused by Pulmonary Infection of Heart Failure Patients. (19th October 2022) - Shi, Licheng; Liu, Jianan; Zhu, Xuanfeng; Li, Tiantian; Wen, Jingli; Wang, Xinyu; Qi, Xu
Abstract : Objectives . Insulin resistance is associated with the prognosis of heart failure (HF) patients. The triglyceride glucose (TyG) index is a simple marker of insulin resistance. However, it remains unclear whether the TyG index is associated with the incidence of readmission in patients with HF. Methods . We enrolled 901 patients with completed records on serum triglyceride and glucose in our study. The TyG index was calculated as log (fasting triglycerides (mg/dL) x fasting glucose (mg/dL)/2). There were 310 cases of readmission and the average TyG index was 7.8 ± 0.7. Restricted cubic spline was fitted to explore the linearity of TyG index associating with 6-month readmission of HF patients. Logistic regression analysis was performed to explore the association between TyG index quartile and the incidence of 6-month readmission. Results . Only the 6-month readmission was significantly different among TyG quartiles, and it was the highest (41.9%) in the lowest quartile (ranging 6.17∼7.36). the TyG index was nonlinearly associated with 6-month readmission (p for nonlinearity = 0.009), with the lower level of TyG index increasing the risk of 6-month readmission. Besides, multivariable logistic analysis showed that the lowest TyG quartile was associated with a higher incidence of 6-month readmission in the unadjusted model (odds ratio [OR] 1.74, 95% confidence interval [CI] 1.18–2.57; p = 0.005 ), partially adjusted model (OR 1.82, 95%CI 1.22–2.72; p = 0.004 ), and fully-adjusted model (OR 1.65, 95%CI 1.09–2.45; p = 0.024 ). The association was consistent across gender and diabetes group. Conclusion . A lower TyG index independently increased the risk of 6-month readmission in HF patients, which could be a prognostic factor in heart failure.